Pengaruh Perceived Organizational Support (POS) dan Role Stress terhadap Job Outcome pada Akuntan Manajemen di Perusahaan-Perusahaan di Kota Surabaya - Hidayatul Khusnah (UNUSA Press, 2017)
Organizational support to employees is an important because can mitigate the negative effects of role stress. The negative effects of the role stress among which reduce job satisfaction, job performance and high turnover intention. Employees who feel themselves noticed by the company will be comfortable in the work so that the performance becomes better. The aim of this study is to investigate the effect of perceived organizational support (POS) to the role stress (role ambiguity, role conflict and role overload) and job outcomes (job satisfaction, job performance and turnover intention). In addition, this study also want investigates the influence of role stress (role ambiguity, role conflictand role overload) to job outcomes (job satisfaction, job performance and turnover intention). This study used a sample of management accountants and staff managementaccountants at companies in the Surabaya. The number of samples in this study were 111 respondents. Testing the hypothesis in this study using Structural Equation Modeling (SEM) with an alternative method of Partial Least Square (PLS) using software WarpPLS 3.0. Results of this study found the negative influence of perceived organizational support(POS) to the role ambiguity and role conflict but did not find the effect of POS on role overload. Other findings in this study is the role ambiguity and role conflict negative effect on job satisfaction, job performance and a positive effect on turnover intention. But different things found on role overload to job satisfaction, job performance, and turnover intention which did not reveal any influence.